Sustainable lightweight foams from hazardous aluminum dross - WEERAPAKDEE, Chayapat; NANKO, Makoto; KUO, Yen-Ling; WATCHARAMAISAKUL, Sukasem; SUZUKI, Kaito; SUZUKI, Seiryu; CHOKKHA, Siriwan (Journal of Metals, Materials and Minerals, 2026)
Aluminum dross is a hazardous byproduct from aluminum industry that causes environmental problems and high disposal cost. This work presents a sustainable route to upcycle secondary aluminum dross into lightweight ceramic foams for insulating refractory applications. Secondary aluminum dross powder was blended with polyethylene (PE) pore-forming agents (30 vol% to 70 vol%) and polyvinyl alcohol (PVA) binder added as a 7.5 wt% aqueous solution (binder contents: 1 vol% and 3 vol%), followed by pressing and sintering at 1400℃. Increasing PE systematically reduced bulk density and increased open porosity. At 70 vol% PE, the foams reached a bulk density of 0.94 g∙cm‒3 and open porosity of 74%, satisfying the Japanese Industrial Standard (JIS) specification for lightweight refractory bricks. The maximum compressive strength was 2 MPa, sufficient for thermal insulation where load-bearing capacity is secondary. X-ray diffraction confirmed a multiphase matrix of α−Al2O3, MgAl2O4, and CaAl12O19, indicating solid-state reactions between alumina and Mg/Ca-bearing phases. Morphology revealed a well-connected porous network stabilized by reaction-bonded bridges, indicating strong interparticle bonding and limited pore coalescence during sintering. This approach can divert over 1000 kg of hazardous waste per ton of secondary aluminum dross processed and cut CO2 emissions by 65% versus alumina routes. The approach promotes circular economy through waste-derived ceramics.